2020
DOI: 10.1093/jat/bkaa105
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl and Driving Impairment

Abstract: The incidence of fentanyl in forensic toxicology analyses in the U.S. has dramatically increased over the past several years. The increase in death cases has been well studied, however little has been reported on the impact to drug impaired driving. Fentanyl driving under the influence of drugs (DUID) case data from 2014 to 2019 is presented. The data was obtained from three toxicology laboratories in the Northeast, Southeast, and Midwest regions of the U.S. Fentanyl whole blood concentrations ranged from 0.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
4
13
0
Order By: Relevance
“…Consistent with other reports on the increase in overdose deaths due to fentanyl, rising concentrations in drivers, and increase in seized drug evidence identified as fentanyl, the Toxicology and Drug Laboratories at SWIFS also observed an increase in fentanyl positive cases each year from 2015 to 2020 [4,14,15]. The number of heroin/6-MAM positive cases remained stable over the six-year period, underscoring concurrent use of heroin and fentanyl as users began to supplement or substitute fentanyl for heroin [16,17].…”
Section: Drug Laboratorysupporting
confidence: 83%
“…Consistent with other reports on the increase in overdose deaths due to fentanyl, rising concentrations in drivers, and increase in seized drug evidence identified as fentanyl, the Toxicology and Drug Laboratories at SWIFS also observed an increase in fentanyl positive cases each year from 2015 to 2020 [4,14,15]. The number of heroin/6-MAM positive cases remained stable over the six-year period, underscoring concurrent use of heroin and fentanyl as users began to supplement or substitute fentanyl for heroin [16,17].…”
Section: Drug Laboratorysupporting
confidence: 83%
“…To the best of our knowledge, this is the first study reporting a decreasing trend in opioid-involved MVC injuries. A study on blood fentanyl concentrations in impaired drivers from 2014–2019 found that their prevalence increased from 4% to 22% in New Hampshire and from 7% to 40% in Florida; however, the illicit use of drugs was apparent in 60% of the fentanyl-involved cases [ 5 ]. In our study, we observed a 39% decrease in the prevalence of prescription fentanyl after the CDC guidelines in 2016, suggesting that policy measures may have been effective in reducing the involvement of prescription fentanyl in MVC injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed a 39% decrease in the prevalence of prescription fentanyl after the CDC guidelines in 2016, suggesting that policy measures may have been effective in reducing the involvement of prescription fentanyl in MVC injuries. The illicit use of opioids is hard to ascertain in fatally injured drivers and fentanyl concentrations in blood are hard to interpret [ 5 ]; therefore, the illicit use of opioids, including fentanyl, was seldomly reported in previous studies. As the illicit use of opioids is an important risk factor for impaired driving, future studies are needed to investigate the impact of the illicit use of opioids on driving safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Rohrig et al report a drastic increase in the percentage of fentanyl‐related DUIDs reported in various geographical locations (north‐ and southeast, midwest) in the United States. Twenty case studies of individuals driving under the influence of fentanyl are also reported with concentrations in blood ranging from 2.0 to 16 ng/mL (5). Increasing reports of fentanyl and fentanyl analog reports in DUID cases presents a major public safety issue that requires the need for routine, advanced forensic toxicological analyses.…”
Section: Introductionmentioning
confidence: 99%